SPEKTRUM SUARA GULAMAH SEBAGAI KAJIAN AWAL PEMBUATAN RUMPON: KASUS DI PERAIRAN TUBAN, JAWA TIMUR - Eko Sulkhani Yulianto; Alfan Jauhari; Dewa Gedhe Raka Wiadnya; Sunardi Sunardi; Muhammad Arif Rahman (Jurnal Teknologi Perikanan dan Kelautan, 2018)
One of the leading commodities in the North Coast of East Java which has a large production is gulamah (Sciaenidae). This fish is one of the marine fisheries commodities that have high potential. Previously the use of gulamah was limited to fresh fish and dried fish. Lately these organs in fish (swimming bladders) have also been widely used and actually have much higher economic value. The high economic value of these commodities has implications for the increasing pressure on exploitation of these fish. In fact, sometimes arrests are made without regard to responsible fishing rules. Gulamah is one type of fish that often makes a â€œcroakâ€ sound in its behavioral activities. Study of the schooling sound spectrum of gulamah (Sciaenidae) as a preliminary study for the manufacture of effective and environmentally friendly Sound-Fish Aggreagating Device as one of the food security instruments for marine fisheries products. So it isexpected that with the introduction of new technologies that are efficient, effective, simple and can provide economic added value for fishermen. Analytical descriptive research method and experimental fishing, the data collected is the sound spectrum data schooling gulamah (Sciaenidae), where data collection is carried out at Tombokboyo Waters, Tuban, East Java. The results showed that gulamah in Tombokboyo waters issued a sound with an average amplitude of around -54,97 dB, an average frequency of 732,129 Hz, with a sound duration of 130 miliseconds